2022
DOI: 10.1111/echo.15423
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the venous duct with abnormal return of the umbilical vein into the superior vena cava: A case report

Abstract: Introduction: Agenesis of the venous duct is rare, with an incidence rate of .04%-.6%.Abnormal drainage of the umbilical vein (UV) to superior vena cava (SVC) is seen in .5% of agenesis of the venous duct cases. We present a case of agenesis of the venous duct with drainage of the UV into the SVC accompanied by tetralogy of Fallot. Case presentation:The fetus was diagnosed with agenesis of the venous duct and tetralogy of Fallot at 29 gestational weeks. The UV directly returned to the SVC. Cardiomegaly and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Genetic studies have revealed insights into the underlying pathogenesis of RSVC agenesis and PLSVC, although further research is needed to elucidate the genetic basis and identify potential risk factors for these venous anomalies (13).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic studies have revealed insights into the underlying pathogenesis of RSVC agenesis and PLSVC, although further research is needed to elucidate the genetic basis and identify potential risk factors for these venous anomalies (13).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these anomalies have been reported across different age groups, from infants to adults. Elgendy et al presented a case of absent RSVC with persistent LSVC diagnosed in a 27-year-old patient through contrast-enhanced computed tomography (Mori et al, 2022).…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations